Case report: Atypical patterns of nystagmus suggest posterior canal cupulolithiasis and short-arm canalithiasis - Helminski, Janet O. (Frontiers in Neurology, 2022)
Background: Atypical positional nystagmus from the posterior canal (PC) may be due to changes in cupular response dynamics from cupulolithiasis (cu), canalithiasis of short arm (ca-sa), or partial/complete obstruction - jam. Factors that change dynamics are position of head in pitch plane, individual variability in location of attachment of PC to utricle and position of cupula within ampulla, and location of debris within short arm and on cupula. In the Dix-Hallpike (DH) position, PC-BPPV-cu could cause no deflection of utricle resulting in no nystagmus or inhibition of the PC afferent resulting in downbeat nystagmus (DBN) with/without torsion lateralized to the uninvolved side. PC-BPPV-ca-sa could cause no nystagmus in the DH position and upbeat nystagmus (UBN) with torsion lateralized to the involved side upon return to sitting. Case description: A 68-year-old female diagnosed with BPPV presented with DBN associated with vertigo in both DH positions and with no nystagmus or symptoms upon sitting up. During the straight head hanging position (SHHP), findings of a transient burst of UBN with left torsion associated with vertigo suggested ipsicanal conversion from left PC-BPPV-cu to canalithiasis. Treatment consisted of modified canalith repositioning procedure (CRP) resulting in complete resolution. Seventeen days later, BPPV recurred. Clinical presentation was no nystagmus/symptoms in both contralateral DH position and SHHP, DBN in ipsilateral DH position with no symptoms, and UBN with left torsion associated with severe truncal retropulsion and nausea upon sitting up. Findings suggested left PC-BPPV-cu-sa and PC-BPPV-ca-sa. Treatment consisted of neck extension, modified CRP, and demi-Semont before complete resolution. Conclusion: Understanding the biomechanics of the vestibular system is necessary to differentially diagnose atypical PC-BPPV. Findings on DHT that suggest PC-BPPV-cu are DBN or no nystagmus in 1 or both DH positions and sometimes SHHP and no nystagmus or no reversal/reversal of nystagmus upon sitting up. Findings that suggest PC-BPPV-ca-sa are no nystagmus in DH positions or DBN in the ipsilateral DH position and UBN with torsion lateralized to involved side upon sitting up.